Challenges in academic speaking for non-native speakers: the case of Libyan students studying in Malaysia - Halali, Ahlam Ali Salim; Ismail, Lilliati; Abd Samad, Arshad; Razali, Abu Bakar; Noordin, Nooreen (UPM Press, 2022)
Malaysian universities’ adoption of English as a medium of instruction provides Libyan international students, who have been reported as the seventh largest ethnic group enrolled in those institutions, with opportunities to pursue various fields of study. However, Libyan students struggle with academic speaking resulting from inadequate prior EFL learning experience characterised by a lack of speaking practice. Consequently, causing communicative incompetency that contributes to language anxiety. Therefore, this study investigates the academic speaking challenges of Libyan students in Malaysian academic settings using an explanatory mixed-mode research design. Data were collected through an online questionnaire, interviews, and a focus group discussion. The research found that Libyan international students faced challenges in academic speaking due to insufficient linguistic knowledge and a lack of prior academic speaking practice. The study further found that the Libyan students’ speaking challenges in the academic setting were affected by cognitive inhibition resulting from communicative incompetency. The qualitative phase of the study revealed that the students were reluctant to engage in academic discourse because of their incompetency in academic speaking skills, which caused anxiety and embarrassment. The study results could inform stakeholders such as the Libyan Ministry of Education about the academic speaking challenges of Libyan students studying abroad. Furthermore, it could lead to improvements in preparatory programs, English teaching practices and materials, and exposure to academic settings in foreign universities to prepare students to further their studies abroad and achieve international academic success.